1954
DOI: 10.1002/hlca.19540370402
|View full text |Cite
|
Sign up to set email alerts
|

Komplexone XXV. Die polarographische Untersuchung von Austauschgleichgewichten. Neue Daten der Bildungskonstanten von Metallkomplexen der Äthylendiamin‐tetraessigsäure und der 1,2‐Diaminocyclohexan‐tetraessigsäure

Abstract: The polarograms of the metal complexes of Ethylenediaminetetraacetic Acid and of 1,2‐Diaminocyclohexane‐tetraacetic Acid are described. In a mixture, containing the metal complex MYv−4 as well as the uncomplexed cation M+v, it is usually possible to determine the concentration of the latter with high accuracy with the aid of a polarograph. Such measurements have been used for the determination of the ratios of the formation constants of the complexes of two metals M and M′, and from these ratios the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1956
1956
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…In the case of Cd(II)-EDTA titration, the ammonia by using the above-determined KCdD value and the numerical values13,16) given in Table 2 can be considered to have a magnitude which can explain well the facts given by Schwarzenbach et al 13) From the facts obtained and the theoretical discussion given above, it can be safely concluded that reasonable KPbD and KcdD values have been determined.…”
Section: The Above Relations Indicate That When Mdis Formed Only Thesupporting
confidence: 62%
“…In the case of Cd(II)-EDTA titration, the ammonia by using the above-determined KCdD value and the numerical values13,16) given in Table 2 can be considered to have a magnitude which can explain well the facts given by Schwarzenbach et al 13) From the facts obtained and the theoretical discussion given above, it can be safely concluded that reasonable KPbD and KcdD values have been determined.…”
Section: The Above Relations Indicate That When Mdis Formed Only Thesupporting
confidence: 62%
“…2 clearly shows that BT forms only normal chelate CoD-with cobalt(II) under the experimental conditions. With the aid of relation (2), the stability constant for CoD-was calculated to be 100.0 by using the log{ Since the kinetic measurements were carried out in solutions containing EDTA and cobalt(II)-EDTA chelate in an excess over BT, the overall exchange reaction of BT and cobalt(II)-EDTA system (1) can be simplified to, (5) whose reaction rate is given by (6) where k's mean the apparent rate constants. Integrating Eq.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pH titration was carried out successfully when the transition metals and calcium were chosen as the first and the second metal ions respectively, and the stability constants for the transition metalcalcium TAPHA chelates (KMCaL) were obtained from Eq. (14). The various equilibrium constants thus obtained are summarized in Tables 3-8.…”
Section: Table 2 Definitions Of Equilibrium Constantsmentioning
confidence: 99%